Changes in quaternary structure of IgG upon reduction of the interheavy-chain disulfide bond. - Seegan, G W (1979)
Reduction of the single disulfide bond between heavy chains in the hinge region of rabbit IgG antibody causes destabilization of the CH2 region of the molecule. Our studies indicate that reduced antibody molecules undergo a large change in quaternary structure in the CH2 region upon aggregation with a small bivalent hapten. The conformational change was observed both in hydrodynamic studies and by electron microscopy. The sizes of native and reduced antibody complexes were measured from electron micrographs. These measurements show that reduction of the hinge disulfide allows the CH2 domains of the antibody to separate under the strain induced by complex formation. The Fab arms, which are clearly seen in the electron micrographs of the native complexes, are extended by a portion of the Fc region to effectively become Facb arms in the reduced complexes. The length of the arms is effectively increased by 23 A. This results in a massive alteration in the quaternary structure of the CH2 region of the molecule, and this may be the basis of many of the effects of mild reduction on the various effector functions of the antibody molecule. These findings also support the open structure of the CH2 region proposed on the basis of crystallographic analyses, and they demonstrate how the interheavy-chain hinge disulfide restricts segmental flexibility in the Fc fragment of the IgG molecule.